Secondary succession patterns in a disturbed sagebrush community in northwest Colorado - Biondini, Mario E., author; Redente, Edward F., author; Colorado State University. Water Resources Research Institute, publisher (Colorado State University. Libraries, 1996)
The relationship between secondary succession, soil disturbance, and soil biological activity were studied on a sagebrush community in the Piceance Basin of northwest Colorado. Four levels of soil disturbance were imposed following vegetation removal: (1) topsoil left in place; (2) topsoil ripped to a depth of 30 cm; (3) topsoil and subsoil were removed to a depth of 1 m, mixed and rep 1aced; and (4) topsoil and subsoil were removed to a depth of 2 m and replaced in a reverse order. Plant species composition, dehydrogenase and phosphatase enzymatic activity, mycorrhizal inoculum potential (MIP), and percent organic matter were the variables measured. Treatment 4 drastically altered the pattern of vegetation succession. Treatments 2, 3, and 4 started with Russian thistle (Salsola iberica) as the dominant species but six years later, Treatments 3, and to lesser extent 2, were similar to the species composition of Treatment 1, dominated by perennia1 grasses and perennia1 forbs. Treatment 4 developed a shrub-dominated community. Both dehydrogenase enzymatic activity and MIP increased with the change from Russian thistle to a vegetation dominated by either perennial grasses and forbs or shrubs. The intensity of disturbance 228 in Treatments 2s 3s and 4 resulted in drastic reductions of dehydrogenase activity and MIPs but in six years they recovered to levels comparable to Treatment 1. Phosphatase enzyme activity and organ i c matter were unre1ated to species composition but related to treatment and time elapsed. In both cases a significant decrease was observed throughout the six-year period.